Green Computing Approaches - A Survey - Dhaini, Mahdi; Jaber, Mohammad; Fakhereldine, Amin; Hamdan, Sleiman; Haraty, Ramzi A. (Informatica, 2021)
The upsurge in global warming and release of greenhouse gases is a major issue that intensified over the past years due to the increasing usage of technological resources in our daily routines. That is why a call for going green in the technological field is highly recommended. This paper reviews various approaches of green computing in five main models - software engineering model, cloud computing, mobile computing, data centers, and the educational sector.